TI_GERICHTE 52.2019.192 vom 27. März 2019 , Revoca della licenza di condurre veicoli a motore per la durata di quattro mesi - TI Tribunale d'appello (2019)
Revoca della licenza di condurre veicoli a motore per la durata di quattro mesi